Mentalizing in psychodynamic and psychoanalytic psychotherapy: basics, applications, case studies - Brockmann, Josef; Kirsch, Holger; Taubner, Svenja (Routledge, 2025)
"Mentalizing in Psychodynamic and Psychoanalytic Psychotherapy explains how mentalization-based therapy (MBT) can be used within the framework of depth psychology and analytical psychotherapies. Josef Brockmann, Holger Kirsch, and Svenja Taubner explain the outstanding importance of mentalizing for contemporary psychoanalysis and assess the essential conceptual innovations of mentalizing, focusing on outpatient individual therapies for patients with personality disorders. The book demonstrates the high connectivity of mentalizing to psychoanalysis and considers the further development of the concept of mentalizing. A practical and research-oriented work, the book documents numerous case studies, and detailed transcripts of treatment dialogs supplemented by extensive commentary to illustrate the practical application of mentalizing. Mentalizing in Psychodynamic and Psychoanalytic Psychotherapy will be of great interest to psychoanalysts and psychoanalytic psychotherapists in training and in practice who are looking to integrate mentalizing into their work"--
Includes bibliographical references and index
Keywords: Case Reports